Mathematical Philosophy - Nasution, Mahyuddin K.M. (Talenta Publisher, 2020)
Mathematics and philosophy are two words with different meanings and the same thing. With various historical evidence, mathematics as the basis of science is not part of or born from philosophy. In the same position in knowledge, mathematics confirm the answers to intimate problem in philosophy. Often there is confusion in philosophy because of conflicting concepts with one another. Mathematics without philosophy does not move swiftly, because without the meanings that are sometimes driven by philosophy. Logically, truth is not well developed in evidence except when mathematics and philosophy get long. It is to provide an understanding of the need for a foundation of truth thought, which generally reveals in the comprehension of mathematics, namely in meta-mathematics and philosophy.